2016
DOI: 10.1186/s13073-016-0295-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a short-term gluten-free diet on the human gut microbiome

Abstract: BackgroundA gluten-free diet (GFD) is the most commonly adopted special diet worldwide. It is an effective treatment for coeliac disease and is also often followed by individuals to alleviate gastrointestinal complaints. It is known there is an important link between diet and the gut microbiome, but it is largely unknown how a switch to a GFD affects the human gut microbiome.MethodsWe studied changes in the gut microbiomes of 21 healthy volunteers who followed a GFD for four weeks. We collected nine stool samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(182 citation statements)
references
References 46 publications
8
155
1
7
Order By: Relevance
“…In a recent study, 21 healthy volunteers were subjected to a gluten-free diet and observed for four weeks. After follow-up period, there was noticed a significant difference in the gut microbiota, where the class of clostridia was significantly reduced (34). In human models, after a six-month of follow-up, the gluten-free diet did not affect autoantibody titers in individuals at high risk of type-1 diabetes.…”
mentioning
confidence: 88%
“…In a recent study, 21 healthy volunteers were subjected to a gluten-free diet and observed for four weeks. After follow-up period, there was noticed a significant difference in the gut microbiota, where the class of clostridia was significantly reduced (34). In human models, after a six-month of follow-up, the gluten-free diet did not affect autoantibody titers in individuals at high risk of type-1 diabetes.…”
mentioning
confidence: 88%
“…These results raise the possibility that the positive effect of a gluten-free diet in patients with IBS may be a nonspecific consequence of reducing the intake of FODMAPs, given that wheat is one of the possible sources of FODMAPs. Another possibility is the potential of the gluten-free diet to alter the composition of the gut microbiota, which has been demonstrated in healthy individuals [46]. However, data are currently lacking regarding the effects of a gluten-free diet on gut microbiota of patients with IBS.…”
Section: Gluten-free Dietsmentioning
confidence: 99%
“…The gut microbiota and its products play an important role in the pathophysiology of celiac disease, and dietary composition can modulate the structure of microbiota. Bonder et al [5] found that in healthy people, the gluten-free diet did not induce major inlammatory or metabolic changes in gut function after 1-month intervention, in contrast to people with celiac disease. However, they observed a decrease in the proportion of Veillonellaceae, considered a pro-inlammatory family frequently reported in patients with inlammatory bowel syndrome.…”
Section: Gluten-free Diet As a Therapy And As A Self-prescribed Foodmentioning
confidence: 99%
“…Nowadays, due to marketing strategies and trends related to healthy foods, as well as self-diagnosis of gluten-/wheat-related disorders, an important part of the population in developed countries is following a gluten-free diet. This diet is currently one of the three most popular food regimen in the world along with the low-carbohydrate and fat-free diets [5].…”
Section: Gluten-free Market and Regulation Of Gluten-free Foodsmentioning
confidence: 99%
See 1 more Smart Citation